Leadership Capabilities and Innovation Performance, a Literature Review - Setiyorini, Mamik; Sobandi, Ade (UNIVERSITAS PAKUAN, 2017)
. In the current VUCA era, change leaders are needed who are expected to be able to adapt to various forms of uncertainty and dynamics of the organization's future. The internal and external dynamics of an organization are an absolute must to pay attention to and continuously update the organization's business strategy. Change leaders need competency to adapt to future uncertainty, namely dynamic capability. Organizations need to be supported by innovation performance to remain superior to others. The research aim is to determine the competencies that leaders must have to be able to work dynamically and identify the factors that influence innovation performance. The method used was a literature review of articles with the theme dynamic capabilities and innovation performance and interviews with respondents in the category of change leaders. The results of this research show that the capabilities that change leaders must have are digital capabilities, dynamic capabilities, flexibility working capabilities, environmental orientation capabilities and adaptive leadership capabilities. And the variables used to assess innovation performance in organizations are digital firm innovativeness, organizational performance, organizational sustainablity, innovation performance.